Analisis pengaruh alokasi dana pembinaan terhadap daya saing komoditi unggulan daerah (studi kasus UMKM petani Kemiri Kabupaten Padang Lawas Utara Provinsi Sumatra Utara) - Harahap, Toharuddin; Handra, Hefrizal; Yonnedi, Efa (Jurnal Paradigma Ekonomika, 2023)
This research aims to understand analysis of the influence of the allocation of development funds on the competitiveness of regional superior commodities (case study of SMEs of candlenut farmers, North Padang Lawas Regency, North Sumatra Province). This study used a qualitative descriptive method. The data used are secondary data obtained through the website of the Directorate General of Fiscal Balance www. djpk.kemenkeu.go.id/ and the Central Statistics Agency for the North Padang Lawas Regency. The results of the study have a partial effect on predicting the analysis of the influence of the allocation of coaching funds (Case Study of Kemiri Small Medium Enterprises, North Padang Lawas Regency, North Sumatra Province). While the results of the study have a partial effect on predicting the competitiveness of regional superior commodities (Case Study of Kemiri Pecan Farmers, North Padang Lawas Regency, North Sumatra Province).